Capacity Building for Integrated Health Post (Posyandu) Cadres Through Nutritional Status Monitoring Training and Local PMT Processing in Musi Banyuasin - Mitayani Purwoko; Rika Puspita Sari MZ; Vina Pramayastri; Jun Harbi; Rahmat Kurniawan; Novi Apriani; Irkhamiawan Ma'ruf; Elva Dwi Harmilia (Universitas Muhammadiyah Palembang, 2026)
One form of community-based health service is Posyandu. Generally, Posyandu cadres are members of the community who do not have a background as medical or health professionals, so in the field, they often face various obstacles and limitations in providing health services. This community service activity was conducted in Musi Banyuasin Regency. A total of 72 Posyandu and nutrition post cadres from nine villages, namely Babat Supat, Babat Ramba Jaya, Sukamaju, Letang, Tri Tunggal, Pangkalan Tungkal, Simpang Tungkal, Mangsang, and Muara Merang villages. The methods used were assessment, material delivery (education), and practice or demonstration. The pre-test and post-test scores showed that this activity succeeded in increasing the knowledge and abilities of Posyandu and nutrition post cadres. Cadres gained a better understanding of using anthropometry and determining the nutritional status of pregnant women, infants, and toddlers. In addition, cadres also better understood and were able to practice preparing balanced nutritious menus for Supplementary Feeding (PMT) at the Posyandu.